Early enforced mobilization after liver resection: A prospective randomized controlled trial. (June 2018) - Ni, Chun-yan; Wang, Zhi-hong; Huang, Zhi-ping; Zhou, Hui; Fu, Li-juan; Cai, Hui; Huang, Xuan-xuan; Yang, Yuan; Li, Hui-fen; Zhou, Wei-ping
Abstract: Objective: This randomized controlled study investigated the feasibility of early ambulation after liver resection and the effect of the amount of activity on postoperative recovery. Methods: A total of 120 patients who underwent liver resection were randomly divided into two groups for the comparative analysis of the following factors: amount of activity, pain control, sleeping state, perioperative gastrointestinal function recovery, incidence of complications and postoperative hospital stay. Results: Compared with the control group, patients undergoing liver resection performing early postoperative ambulation had faster gastrointestinal function recovery (First exhaust time 2.2 ± 1.4 vs. 3.3 ± 2.3 p < 0.01; First flatus time 2.3 ± 1.7 vs. 3.1 ± 2.5 p = 0.04) and shorter postoperative hospital stays (6.6 ± 2.3 vs. 7.7 ± 2.1 p = 0.01), with statistically significant differences. There was no significant difference in the incidence of postoperative complications between the two groups (p > 0.05). Conclusion: Early ambulation after liver resection is safe and feasible. It can reduce the patient's pain and economic burden, increase the patient's comfort, reduce the nursing workload, achieve rapid recovery, and improve patient satisfaction. Highlights: Quantitative study on early enforced mobilization for ERAS of liver resection. Early enforced mobilization after liver resection is safe and feasible. Wireless smart wristband available for clinical observation.